2009
DOI: 10.1111/j.1600-0528.2009.00470.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with early‐stage diagnosis of oral and pharyngeal cancer

Abstract: These results emphasize the importance of periodic and thorough OPC examinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 33 publications
2
40
0
7
Order By: Relevance
“…20 Of patients diagnosed with oral cancer, most can retrospectively pinpoint symptoms attributable to cancer and the majority of patients diagnosed with oral cancer report presenting as a result of their symptoms. 10,21 This being said, symptom recognition is not a reliable method of detecting tumours at an early stage since about 25% of oral cancers remain asymptomatic until they reach an advanced size. 22 Although tumours may not necessarily be detected at an early stage, attribution of symptoms to cancer can at least lead to earlier detection.…”
Section: Australian Dental Journalmentioning
confidence: 99%
“…20 Of patients diagnosed with oral cancer, most can retrospectively pinpoint symptoms attributable to cancer and the majority of patients diagnosed with oral cancer report presenting as a result of their symptoms. 10,21 This being said, symptom recognition is not a reliable method of detecting tumours at an early stage since about 25% of oral cancers remain asymptomatic until they reach an advanced size. 22 Although tumours may not necessarily be detected at an early stage, attribution of symptoms to cancer can at least lead to earlier detection.…”
Section: Australian Dental Journalmentioning
confidence: 99%
“…40 Of patients diagnosed with oral cancer, most can retrospectively pinpoint symptoms attributable to cancer and the majority of patients diagnosed with oral cancer report presenting as a result of their symptoms. 16,46 This being said, symptom recognition is not a reliable method of detecting tumours at an early stage since about 25% of oral cancers remain silent until they reach an advanced size. 21 Although tumours may not necessarily be detected at an early stage, attribution of symptoms to cancer can at least lead to earlier detection.…”
Section: Lesion Factors Contributing To Delaymentioning
confidence: 99%
“…One study did however report that most individuals in the USA diagnosed with oral cancer had health insurance coverage, and those that had no coverage did not exhibit excessive delay. 46 A study performed in the UK reported that an oral cancer patient waited to see a free NHS dentist rather than be seen immediately by a private dentist, for which a fee would be charged. 8 Only three out of 44 patients interviewed in England identified costs of a dental check up to be a large barrier.…”
Section: Socio Demographic Factors Contributing To Delaymentioning
confidence: 99%
See 2 more Smart Citations